Endoplasmic reticulum stress and autophagy dysregulation in alcoholic and non-alcoholic liver diseases - Yun Seok Kim; Sang Geon Kim (Clinical and Molecular Hepatology, 2020)
Alcoholic and non-alcoholic liver diseases begin from an imbalance in lipid metabolism in hepatocytes as the earliest response. Both liver diseases share common disease features and stages (i.e., steatosis, hepatitis, cirrhosis, and hepatocellular carcinoma). However, the two diseases have differential pathogenesis and clinical symptoms. Studies have elucidated the molecular basis underlying similarities and differences in the pathogenesis of the diseases; the factors contributing to the progression of liver diseases include depletion of sulfhydryl pools, enhanced levels of reactive oxygen and nitrogen intermediates, increased sensitivity of hepatocytes to toxic cytokines, mitochondrial dysfunction, and insulin resistance. Endoplasmic reticulum (ER) stress, which is caused by the accumulation of misfolded proteins and calcium depletion, contributes to the pathogenesis, often causing catastrophic cell death. Several studies have demonstrated a mechanism by which ER stress triggers liver disease progression. Autophagy is an evolutionarily conserved process that regulates organelle turnover and cellular energy balance through decomposing damaged organelles including mitochondria, misfolded proteins, and lipid droplets. Autophagy dysregulation also exacerbates liver diseases. Thus, autophagy-related molecules can be potential therapeutic targets for liver diseases. Since ER stress and autophagy are closely linked to each other, an understanding of the molecules, gene clusters, and networks engaged in these processes would be of help to find new remedies for alcoholic and non-alcoholic liver diseases. In this review, we summarize the recent findings and perspectives in the context of the molecular pathogenesis of the liver diseases.